Relación entre marca comercial de pack reproductivo y porcentaje de preñez a la IATF - Prieto, Paula Noelia; Etchepare, Paulo; Bordón, Ángel; Ramirez, Cristian Ariel; Da Luz, Miguel; Stahringer, Rodolfo Carlos (Instituto de Reproducción Animal de Córdoba, 2024)
Poster